2001
DOI: 10.1038/sj.onc.1204713
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirement of the last C-terminal tail of Met receptor for cell transformation and invasiveness

Abstract: Biological responses to Hepatocyte Growth Factor are mediated by the tyrosine kinase receptor encoded by the Met oncogene. Under physiological conditions, Met triggers a multi-step genetic program called`invasive growth' including cell-dissociation, invasion of extracellular matrices and growth. When constitutively activated, Met can induce cell transformation and metastasis. Phosphorylation of two docking tyrosines in the receptor tail is essential for all biological responses. To investigate the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The pcDNA3 expression vector encoding Gab1 was a kind gift of P. Gual and S. Giordano (Instituto per la Ricerca e la Cura del Cancro, Candiolo, Torino, Italy; ref. 27). The pCMV6-CrkII plasmid was from OriGene Technologies, Inc. (Rockville, MD).…”
Section: Methodsmentioning
confidence: 99%
“…The pcDNA3 expression vector encoding Gab1 was a kind gift of P. Gual and S. Giordano (Instituto per la Ricerca e la Cura del Cancro, Candiolo, Torino, Italy; ref. 27). The pCMV6-CrkII plasmid was from OriGene Technologies, Inc. (Rockville, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, these two tyrosines are not absolutely required for Gab1 phosphorylation in mouse hepatocytes expressing physiological levels of Met or in COS-7 cells transiently expressing the Tpr-Met oncoprotein. Mutation of tyrosines 1349 and 1356 reduces, but does not abolish, Gab1 phosphorylation in these two cell lines (13,26). In contrast to the situation in T47D, COS-7 cells, or hepatocytes, in MDCK cells the two tyrosines are essential for Gab1 phosphorylation (42).…”
Section: Discussionmentioning
confidence: 79%
“…In one previous study examining tyrosines 1349 and 1356 in Met, mutation of these residues to phenylalanine was found to cause a nearly complete defect in Met-dependent Gab1 phosphorylation (42). However, in other reports significant Gab1 phosphorylation was detected in cells expressing Met in which the docking site tyrosines were mutated or deleted (13,26). The reasons for these differences in Gab1 phosphorylation are not understood but may be due to the different cell lines employed.…”
Section: Inlb-dependent Entry Ofmentioning
confidence: 77%
“…We observed that Tyr(P)-1349 was able to recruit primarily SH2 domains from PLCG1 and SH2D1B with moderate affinity. c-Met Tyr(P)-1365 has been shown to be important for full enzymatic activity of the receptor and has been suggested to recruit downstream signaling mediators (40). We identified interactions with SH2 domains from several c-Src family kinases, tensin family, PLCG1, RASA1, SH2D1A, and SH2D1B proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%